ECONOMIC FREEDOM & HAPPINESS INEQUALITY: FRIENDS OR FOES?. (4th August 2016) - Bennett, Daniel L.; Nikolaev, Boris
Abstract : This article examines the relationship between economic freedom and happiness inequality for a large sample of countries. We find that economic freedom is negatively associated with happiness inequality and robust to several alternative measures of happiness inequality, including the standard deviation, mean absolute difference, coefficient of variation, and Gini coefficient. Among the economic freedom areas, legal system and sound money are negatively correlated with happiness inequality. Drawing on the Engerman‐Sokoloff hypothesis, we use a measure of factor endowments as an instrument for economic freedom to provide a further robustness test, finding a negative association between economic freedom and happiness inequality. ( JEL D63, I31, P16)